Diversity and origin of quartz cements in continental carbonates: Example from the Lower Cretaceous rift deposits of the South Atlantic margin. (January 2019) - Teboul, Pierre-Alexandre; Durlet, Christophe; Girard, Jean-Pierre; Dubois, Ludivine; San Miguel, Galo; Virgone, Aurélien; Gaucher, Eric C.; Camoin, Gilbert
Abstract: Silica precipitation in continental carbonates is a common process occurring during sedimentation and diagenesis. The Lower Cretaceous rift deposits of the South Atlantic equatorial margin, which are intensively explored by petroleum companies, provide good examples of such silicifications in carbonates, exhibiting a wide diversity of petrographic habit of early to late quartz cements. In order to understand the palaeoenvironmental and diagenetic conditions leading to this diversity, we integrated detailed petrography of diagenetic sequences and quartz habit with δ 18 Oquartz measurements (by SIMS) of individual cements observed in samples from the offshore and onshore basins of the West African margin. The petrographic description highlights the omnipresence of early fibrous microquartz cements exhibiting either length-fast or length-slow habit, in addition to laminated microquartz and micro- or mega-quartz forms. Amongst the isotopic analysis, the δ 18 Oquartz data show that length-slow cements are generally strongly enriched in 18 O (δ 18 Oquartz ranging from 31 to 37‰ SMOW), whereas length-fast forms show less elevated values (<32‰ SMOW). The highest δ 18 Oquartz values for fibrous microquartz are interpreted to reflect precipitation from evaporated meteoric fluids at temperatures >25 °C and <100 °C. The alkalinity required to favor the precipitation of length-slow fibrous microquartz cements is probably related to fluid/rock interactions with underlying mantel-related or basic volcanic rocks. Such interactions would be in agreement with the recent geodynamic models of the South Atlantic passive margin. The length-fast fibrous microquartz associated with δ 18 Oquartz values ranging from 27 to 32‰ SMOW, probably reflect precipitation from moderately to non evaporated, fairly neutral to acid, fluids. The partial dissolution of carbonate cements prior to quartz cementations represents the signature of those acidic conditions. We therefore suggest that acidic pH was obtained through fluid/rock interactions with the intermediate to acid volcanic rocks encountered along the palaeohydrological pathway. Other quartz phases, such as the megaquartz cement, exhibit highly variable δ 18 Oquartz values ranging from 20 to 40‰. This variation may reflect significant variation in temperature conditions (between 100 and 200 °C) or changes in fluid δ 18 O at the small scale. For these populations of non-fibrous quartz cement, the very high δ 18 Oquartz values may reflect a contribution of fluids that have either suffered strong evaporation or strong water/rock interaction. Highlights: Quartz cements show extremely high δ 18 O values (up to 40‰). In situ δ 18 O analyses reveal a variability between and within different quartz generations. δ 18 O associated with length fast and length slow quartz habits helps to understand paleofluid history.